Biogas plants and surplus generation: Cost driver or reducer in the future German electricity system?. (October 2017) - Lauer, Markus; Thrän, Daniela
Abstract: The proportion of (intermittent) renewable energy in the German electricity system is set to continuously increase over the next decades. This brings along with it the challenge of balancing demand and supply. For this paper, we analyzed the cost efficiency of reducing surplus generation to reduce greenhouse gas emissions in the German electricity system for the period of 2016–2035 through (flexible) biogas plants, taking into consideration different biogas extension paths and modes of operation. We assessed flexible power generation in biogas plants using a quotient of remuneration and surplus generation called the average integration costs of surplus generation (AICSG). We defined the AICSG, which can be interpreted as a new approach to assess and to compare the cost efficiency of flexibility options. Increasing the capacities of flexible biogas plants decreases future surplus generation by up to 35% compared to if these installments were phased out. The best AICSG value was generated in a scenario that had a low rate of constructing new biogas plants. In conclusion, the system integration of intermittent renewable energies requires further technologies that result in additional costs. Therefore, biogas plants are one option for improving the system integration of intermittent renewable energies. Highlights: Cost efficiency of reducing surplus generation through biogas plants in Germany. The average integration costs of surplus generation are used as a benchmark. Flexible biogas plants reduce future surplus generation. Cost efficiency of flexible biogas plants depends on the renewable portfolio.